SMART LIBRARY DESIGN FOR FLOWAUTOMATIONANDEFFICIENCY IMPROVEMENT - Fanny Nimita; Amanda Rosetia (Ide dan Dialog Desain Indonesia (Idealog), 2023)
The library is a public facility that has a very positive impact on the wider community. However, the rapid development of technology and information has resulted in many conventional libraries beingabandoned by current library users, namely generation Z. The systems used in conventional libraries cannolonger meet the needs of generation Z who want to do things independently by getting fast, easy and ef icient results. simple. Thus, the design of a self-service library based on smart architecture is a solution tosolvethis problem. With the use of Radio Frequency Identification (RFID) technology, Internet of Things (IoT), and Building Automation System (BAS) systems in designing self-service libraries, a library building canbereferred to as a smart library. The design of this smart library aims to increase ef iciency andflowautomation in the library so that it can meet the needs of generation Z and can be used properly by otherlibrary visitors. The method used in this study is a descriptive qualitative method by comparing case studiesin 3 buildings to analyze the novelty elements that the researcher wants to get. So that this researchcanprovide recommendations on the organization of library building spaces with automation flowto increaseef iciency. Keywords : Smart Library, Self-Service, RFID (Radio Frequency Identification), IoT (Internet of Things), BAS (Building Automation System)